IMPROVING SOCIAL STUDIES LEARNING OUTCOMES USING IMAGE MEDIA FOR GRADE IV STUDENTS, MIS AL-KHAIRAT DELI TUA - Juniko Esra Tarigan (Jurnal Ilmiah Teunuleh, 2020)
This study aims to improve social studies learning by using Image Media in MIS Al-Khairat Deli Tua for the 2020/2021 School Year. This research includes classroom action research. The average value of the class in the pre-cycle was 65.76 while in the first cycle it reached 71.92. The percentage of completion of students who have reached KKM from all students has also increased. In the pre-cycle it was 48%, while in the first cycle it reached 60%. In the first cycle, the percentage of student completion has not reached KKM is still less than 75%, so the research continues to cycle II. From cycle I to cycle II, it increased by 4.98 from 71.92 to 76.9. Apart from the average class, an increase also occurred in the student's completion score. The number of students who scored ?70 from pre-cycle to cycle I increased by 3 or 12% of all students, while from cycle I to cycle II as much as 7 or 28% of all students. Based on this, the criteria for success in the pre-cycle have not been achieved because the achievement of KKM is only 48% of all students. Then in cycle I it increases to 60% and in cycle II it increases again to 88%. Based on this data, this research has been achieved because more than 75% of students achieved KKM.